Individual and community-level predictors of maternal alcohol consumption during pregnancy in Gondar town, Northwest Ethiopia: a multilevel logistic regression analysis - Alemu Earsido Addila; Telake Azale; Yigzaw Kebede Gete; Mezgebu Yitayal (BMC, 2021)
Abstract Background Prenatal alcohol consumption is a serious public health concern that is considered as one of the preventable risk factors for neonatal and childhood morbidity and several adverse pregnancy outcomes. This study aimed to determine the individual- and community-level predictors of maternal alcohol consumption during pregnancy in Gondar town, Northwest Ethiopia. Methods A community-based cross-sectional study was conducted among pregnant women in Gondar town from 13 June to 24 August 2019. A cluster random sampling technique was used to select 1237 pregnant women. Data collection was carried out using the AUDIT-C pretested standard questionnaire. Bivariable and multivariable multilevel logistic regression analyses were computed to identify predictors of alcohol consumption using the odds ratio, 95% CI, and p-value < 0.05. Results The prevalence of alcohol consumption during pregnancy was found to be 30.26% (95% CI: 27.74%, 32.91%). The study revealed that pregnant women who have a low knowledge level on harmful effect of alcohol consumption (AOR = 3.2; 95% CI: 1.9, 5.4), positive attitude towards alcohol consumption (AOR = 7.5; 95% 5, 11), history of pre-pregnancy alcohol consumption (AOR = 4.8; 95% CI: 3.4, 6.9), whose partner consume alcohol (AOR = 3.9; 95% CI: 2.5, 6), a perception that alcohol consumption is culturally or socially acceptable (AOR = 3.6; 95% CI: 2.4, 5.3), who were encouraged by their partners to consume alcohol (AOR = 4; 95% CI: 1.9, 8) were significantly associated with pregnancy alcohol consumption. Concerning the community-level characteristics, who had not ever heard/media exposure about the risk of alcohol drinking during pregnancy (AOR = 3; 95% CI: 1.7, 5.5), and who were from low community women's education attainment (AOR = 4; 95% CI: 2.2, 7.7) were statistically significant predictors of alcohol consumption during pregnancy. Conclusions The study revealed that alcohol consumption during pregnancy is prevalent in Gondar town. Both individual- and community-level predictors were found to be associated with alcohol consumption during pregnancy. Policymakers may take into account these predictors for individual and community-based interventions to which our results appear to point.